Axial Unipolar Eddy Current Brake Performance Characteristics Against Heat Increase in Rotor - Mufti Reza Aulia Putra; Dominicus Danardono Dwi Prija Tjahjana; Muhammad Nizam; Zainal Arifin; Bhre Wangsa Lenggana; Inayati Inayati (Automotive Experiences, 2023)
The development of transportation technology in the automotive sector such as electric vehicles is increasingly advanced. One technology that is needed quite a lot is the development of supporting technology for electric vehicle braking. The use of regenerative braking on light electric vehicles such as 2-wheeled vehicles is not efficient because of its low weight. The use of Eddy Current Brake (ECB) can be a solution for braking support needs. This is because the ECB is a braking system that has the advantage of a lightweight design but still relies on the frictionless principle. However, in addition to its advantages, the eddy current brake is still in the early stages of its research with efficiency that still needs to be developed. In the discussion of the ECB, heat generation is one of the interesting topics to be discussed. Specifically, the study of the characteristics of the unipolar ECB axial performance on heat generation events has not yet been discussed. So this article aims to discuss these events with a simulation process and simple mathematical calculations. Design optimization is done to get the best value. As a result, the use of eddy current brakes with conductor disks using slots, can improve the performance of the ECB on the torque side and cooling side. Thus, this article is a good contribution to the sustainability of ECB research in both the general and automotive fields.